Clinical Benefit Assessment of Vismodegib Therapy in Patients With Advanced Basal Cell Carcinoma. (7th July 2014) - Dreno, Brigitte; Basset‐Seguin, Nicole; Caro, Ivor; Yue, Huibin; Schadendorf, Dirk
Abstract : Purpose: Vismodegib was approved for the treatment of advanced basal cell carcinoma (aBCC) based on the pivotal ERIVANCE BCC study. The primary endpoint (objective response rate [ORR]) was assessed 9 months after the last patient was enrolled. To confirm the clinical benefit of vismodegib, an additional analysis was performed 12 months after the primary analysis. Materials and Methods: ERIVANCE BCC was a multicenter, nonrandomized, two‐cohort study of 104 patients with histologically confirmed aBCC. Patients received 150 mg oral vismodegib daily until disease progression, intolerable toxicity, or withdrawal. An independent review panel comprising three expert clinicians reviewed patient photographs individually and as a consensus panel to evaluate baseline disease severity and clinical benefit after vismodegib treatment in 71 patients with locally advanced BCC (laBCC). Results: Sixty‐three patients were efficacy evaluable; baseline and postprogression photographs for 61 were available for review. Baseline disease severity was judged as 5 or 4 (very severe or moderately severe) in 71.4%. Clinical benefit was observed in 76.2% (significant: 65.1%; some: 11.1%). Interpanelist agreement (maximum difference ≤1 point among panelists' scores in 65.1% and 87.3% of patients for clinical benefit and baseline disease severity, respectively) and correlation between individual and panel reviews were strong. Clinical benefit scores showed good concordance with the protocol‐specified ORR obtained by an independent review facility and with investigator‐assessed response. Conclusion: Clinical benefit assessed by independent review based on expert clinical judgment provides strong evidence that treatment with vismodegib results in clinically meaningful and durable responses in patients with laBCC. Abstract : In this analysis, photographs of advanced basal cell carcinoma (BCC) lesions were used to better characterize both the severity of the disease at baseline and the clinical benefit derived from treatment with vismodegib in the ERIVANCE BCC study. Clinical benefit assessed by independent review based on expert clinical judgment provides strong evidence that treatment with vismodegib results in clinically meaningful and durable responses in patients with locally advanced BCC.